DESIGN AND DEVELOPMENT OF FAST CHARGING BATTERY USING FUZZY LOGIC CONTROL TECHNIQUE - Muhammad Nizam; Naji Abdalaziz Ali (Universitas Sebelas Maret (UNS), 2019)
Battery charging is an important issue when it is associated with battery life and cycle performance. The aim of this research is to design and promote fast battery chargers using fuzzy logic control techniques (FLC) for LiFePO4 batteries have been developed. The proposed charger is controlled by voltage and current to activate the PWM duty. The results show that the proposed battery charger has the potential to accelerate charging up to 37% at the rate when charging 2C. This means it is faster than the existing filling. The charger proposed by the FLC method is also capable of charging LiFePO4 batteries with greater efficiency, which is 82%. It can be concluded that the FLC application method has better performance than the CC-CV method